India: Information Village Research Project (MS Swaminathan Research Foundation) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The Information Village Research Project is an experiment in electronic knowledge delivery. Ten villages in Tamil Nadu have been connected using a hybrid wired and wireless network of PCs, phones, VHF duplex radio devices and email through dial-up telepho